Pengajaran yang Efektif terhadap Perkembangan Psikologi Peserta Didik - Nurul Hidayah Al Haj; Fauziah Nasution; M Aulia Fadlan Aminullah; Nadiaul Haq (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Effective teaching is teaching that has been planned and has a positive impact on learning, so that it is easily conveyed to students. Effective teaching is needed by students, in order to easily understand the material presented. In essence, effective teaching must have been prepared by the teacher, because the teacher will face students with various kinds of characters, so that a teacher has adjusted the strategy used in teaching. None other than, besides the role of the teacher, effective teaching also plays a very important role in the character development of students. So that effective learning is able to develop the psychology of students. From the results of a teacher's research on student psychology, it is able to help teachers adapt methods, media to learning strategies for the psychological state of students, which has a positive impact on the psychological development of students. Keywords: Effective Teaching, Influence, Student Psychology